Transcriptome Analysis of Ramie (Boehmeria nivea L. Gaud.) in Response to Ramie Moth (Cocytodes coerulea Guenée) Infestation. (29th February 2016) - Zeng, Liangbin; Shen, Airong; Chen, Jia; Yan, Zhun; Liu, Touming; Xue, Zhaodong; Yu, Yongting
Abstract : The ramie moth Cocytodes coerulea Guenée (RM) is an economically important pest that seriously impairs the yield of ramie, an important natural fiber crop. The molecular mechanisms that underlie the ramie-pest interactions are unclear up to date. Therefore, a transcriptome profiling analysis would aid in understanding the ramie defense mechanisms against RM. In this study, we first constructed two cDNA libraries derived from RM-challenged (CH) and unchallenged (CK) ramie leaves. The subsequent sequencing of the CH and CK libraries yielded 40.2 and 62.8 million reads, respectively. Furthermore, de novo assembling of these reads generated 26, 759 and 29, 988 unigenes, respectively. An integrated assembly of data from these two libraries resulted in 46, 533 unigenes, with an average length of 845 bp per unigene. Among these genes, 24, 327 (52.28%) were functionally annotated by predicted protein function. A comparative analysis of the CK and CH transcriptome profiles revealed 1, 980 differentially expressed genes (DEGs), of which 750 were upregulated and 1, 230 were downregulated. A quantitative real-time PCR (qRT-PCR) analysis of 13 random selected genes confirmed the gene expression patterns that were determined by Illumina sequencing. Among the DEGs, the expression patterns of transcription factors, protease inhibitors, and antioxidant enzymes were studied. Overall, these results provide useful insights into the defense mechanism of ramie against RM.